2011
DOI: 10.4067/s0716-97602011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hyorhinis and Mycoplasma fermentans induce cell apoptosis and changes in gene expression profiles of 32D cells

Abstract: Infection of mycoplasmas has been linked to various human diseases including arthritis, pneumonia, infertility and cancer. While Mycoplasma hyorhinis and Mycoplasma fermentans have been detected in gastric adenocarcinomas, the mechanisms underlyine the pathogenesis are unknown. In this study, cell growth kinetics, Hoechst 33258 staining, DNA ladder assays, Western blotting analysis and cDNA microarray assays were performed to investigate the roles of M. hyorhinis and M. fermentans during infection of mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Additionally, we observed decreased confluence of MGC803 cells upon M. hyorhinis infection for 48 h, an indicative of increased cell death or/and decreased proliferation. Previous studies showed that acute infection of M. hyorhinis could initiate apoptosis in distinct cell lines [39,40], while we also found stable infection of M. hyorhinis in AGS and MGC803 cells could promote colony formation [6]. Collectively, results of previous reports and our present study demonstrate pleiotropic impacts of M. hyorhinis on cellular phenotypes.…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, we observed decreased confluence of MGC803 cells upon M. hyorhinis infection for 48 h, an indicative of increased cell death or/and decreased proliferation. Previous studies showed that acute infection of M. hyorhinis could initiate apoptosis in distinct cell lines [39,40], while we also found stable infection of M. hyorhinis in AGS and MGC803 cells could promote colony formation [6]. Collectively, results of previous reports and our present study demonstrate pleiotropic impacts of M. hyorhinis on cellular phenotypes.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies demonstrated that the number of cleared apoptotic neutrophils and expression of proinflammatory cytokines are elevated in mice with MPP and causes more severe lung inflammation and higher mortality rates (27). Infection with M. pneumoniae can lead to an imbalance in inflammatory responses that induce the transition from apoptosis to cell death, thereby increasing the severity of lung inflammation (28). The strong association between inflammation and cell survival is reflected by the high IL-6 levels, which suppress cell apoptosis by regulating all hallmarks and multiple signaling pathways involved in inflammation (29).…”
Section: Discussionmentioning
confidence: 99%
“…1 a). Although previous studies showed that M. fermentans infection promotes immortalization of Epstein-Barr virus (EBV)-infected human peripheral blood mononuclear cells 17 and induces apoptosis in 32D cells 18 , infected SH-SY5Y cells showed more propidium iodide (PI)-staining and weaker annexin V-staining than uninfected controls (Fig. 1 b), indicating that M. fermentans induces necrotic neuronal cell death, not apoptosis.…”
Section: Resultsmentioning
confidence: 94%